2011
DOI: 10.1002/jmv.22116
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level persistence of human papillomavirus 16 DNA in a cohort of closely followed adolescent women

Abstract: Most human papillomavirus (HPV) infections in young women become undetectable by standard assays after a few months. It is possible that many HPV infections do not actually clear, but persist at very low levels for years, becoming detected again later in life. The purpose of this study is to describe HPV 16 clearance, reappearance, and low-level persistence in a cohort of adolescent women. Adolescent women (N = 66), not vaccinated against HPV, were recruited from 1998 to 2008 into a longitudinal study. Self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…HPV infections are common, and it is estimated that approximately 75% to 80% of sexually active individuals will become infected in their lifetime (88,89). Most women become infected shortly after becoming sexually active, and the highest prevalence is seen in women under age 25.…”
Section: Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…HPV infections are common, and it is estimated that approximately 75% to 80% of sexually active individuals will become infected in their lifetime (88,89). Most women become infected shortly after becoming sexually active, and the highest prevalence is seen in women under age 25.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Most women become infected shortly after becoming sexually active, and the highest prevalence is seen in women under age 25. Common risk factors for HPV infection in young women include earlier age of onset of sexual activity, two or more sexual partners in the previous year, and coinfection with Chlamydia trachomatis, herpes simplex virus, or bacterial vaginosis (89,90). Cross-sectional studies indicate a second peak of infection in women aged 35 to 54 years, which corresponds to the age of highest incidence of cervical cancer.…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies using highly sensitive PCR-based tests to measure HPV DNA have reported that recurrent detection of an HPV type after a period of non-detection is common, ranging from around 8% to 19.4% (13). Weaver, et al, reported that samples testing HPV16 negative in between runs of HPV16 DNA positivity by standard consensus primer PCR (linear array, LA) were found to be HPV16 positive when more sensitive type-specific amplification assays were used, suggesting that recurrent detection is more likely to represent viral load fluctuations of a persistent infection or periods of latency and reactivation, rather than re-infection of a previously cleared viral type (4). …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, low level persistence may signify containment of HPV-infected cells by cellular immunity resulting in a small lesion that may be difficult to adequately sample by standard methods. Therefore, the clinical significance of low level persistent infection of HPV and the appropriate interpretation of low level HPV DNA existence become more important [21]. …”
Section: Discussionmentioning
confidence: 99%